Econometric Analysis of Impact on Economic Growth of Education Expenditures in Turkey - Kilinc Savrul, Burcu; TUNÇ, Özge (Journal of Applied And Theoretical Social Sciences, 2021)
Education is one of the most important factors contributing to the progress of countries, their welfare, and the level of economic and social development. For this reason, spending on education is of great importance. There fore, the study aims to investigate the effect of education expenditures in Turkey on economic growth. In order to determine the relationship between education expenditures and economic growth, classical stationarity tests and unit root test with multiple structural break were applied in the study. The relationship of cointegration was questioned with the cointegration test with multiple structural breakages and VECM variance decomposition was performed with causality analysis. As a result of the analysis, although it was seen that there is a statistically significant positive relationship between education expenditures and economic growth in the long run, no relationship has been determined in the short run. In addition, when Granger Causality Analysis was applied, the existence of a one-way causality relationship from economic growth to education expenditures has been determined. To sum up, the study showed that education expenditure is an important part of economic growth and revealed the importance of increasing education investments in order to create human capital that will accelerate growth while planning education policies